2008
DOI: 10.1155/2009/641941
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Hepatitis C Virus in Hemodialysis Patients in British Columbia: Follow‐up after a Possible Breach in Hemodialysis Machines

Abstract: BACKGROUND: A possible breach of the transducer protector in specific dialysis machines was reported in June 2004 in British Columbia (BC), which led to testing of hemodialysis patients for hepatitis C virus (HCV), hepatitis B virus (HBV) and HIV. This testing provided an opportunity to examine HCV incidence, prevalence and coinfection with HBV and HIV, and to compare anti-HCV and HCV polymerase chain reaction (PCR).METHODS: The results of hemodialysis patients who were dialyzed on the implicated machines (65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
10
2
3
Order By: Relevance
“…The current study results were in contrast with those of Tu et al (40), which demonstrated significant relationship between HCV and HBV infection in patients undergoing hemodialysis. The increasing use of HBV vaccine and screening the blood units result in remarked decrease in HBV infection.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study results were in contrast with those of Tu et al (40), which demonstrated significant relationship between HCV and HBV infection in patients undergoing hemodialysis. The increasing use of HBV vaccine and screening the blood units result in remarked decrease in HBV infection.…”
Section: Discussioncontrasting
confidence: 99%
“…7,9,31 These circumstances could explain others’ findings of increased risk of HCV infection associated with receiving dialysis on the same machine following an HCV-positive patient or on the same shift with HCV-positive patients, and being connected to the dialysis machine by the same staff member who had connected an HCV-positive patient. 25,27,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…These HCV antibody seroconversions occurred in seven hospitals within five different countries (Zampieron et al 2006). In the WHO Americas region, HCV prevalence among hemodialysis patients are 7.1% in Mexico (Paniagua et al 2010), 5.4% in Canada (Tu et al 2009), and11% in Brazil (Freitas et al 2008). To sum up, it appears that HCV prevalence in hemodialysis patients of the WHO Eastern Mediterranean region is significantly higher than hemodialysis patients of the European, Americas and Western Pacific regions.…”
Section: Authormentioning
confidence: 99%